Fractional-Order Equivalent Circuit Representation of Sucrose Solutions Electrical Impedance Measured in Bipolar Configuration - Duckworth, Colin; Šotner, Roman; Jeřábek, Jan; Freeborn, Todd (IEEE, 2025)
In this work, the alteration in electrical impedance of a liquid (unsweetened FuzeTea) with varying increases in sucrose concentrations (up to 785 mM) was investigated. The aim was to further understand how changes in liquid solutions with adulterants (in this case sucrose) change the electrical impedance as a potential method for food quality monitoring. The electrical impedance was measured from 100 Hz to 1 MHz using gold and platinum electrodes, then numerical optimization was applied to collected datasets to estimate the model parameters of a fractional-order equivalent circuit model to best represent the data. This model demonstrated less than 2% impedance magnitude and less than 6% impedance phase deviation compared to the experimental data. Overall, the model parameter representing the liquid resistance showed large increases for increasing concentrations of sucrose, suggesting that it may be a potential marker for assessing sucrose adulterants in liquid solutions.

In this work, the alteration in electrical impedance of a liquid (unsweetened FuzeTea) with varying increases in sucrose concentrations (up to 785 mM) was investigated. The aim was to further understand how changes in liquid solutions with adulterants (in this case sucrose) change the electrical impedance as a potential method for food quality monitoring. The electrical impedance was measured from 100 Hz to 1 MHz using gold and platinum electrodes, then numerical optimization was applied to collected datasets to estimate the model parameters of a fractional-order equivalent circuit model to best represent the data. This model demonstrated less than 2% impedance magnitude and less than 6% impedance phase deviation compared to the experimental data. Overall, the model parameter representing the liquid resistance showed large increases for increasing concentrations of sucrose, suggesting that it may be a potential marker for assessing sucrose adulterants in liquid solutions.
Fractional-Order Equivalent Circuit Representation of Sucrose Solutions Electrical Impedance Measured in Bipolar Configuration
Keywords: Gold; Liquids; Impedance measurement; Platinum; Data models; Numerical models; Impedance; Integrated Circuit modeling; Sugar; Monitoring; Gold; Liquids; Impedance measurement; Platinum; Data models; Numerical models; Impedance; Integrated Circuit modeling; Sugar; Monitoring